Inclusive Innovation in a Time of Repression: The Case of the Wilvan School of Dance - Barends, Zenariah (Graduate School of Business (GSB), 2024)
There has been minimal emphasis in scholarship in studying and understanding inclusive social innovation within smaller community-based organisations, its intersection with the performing arts, resistance and the struggle for social change in Apartheid South Africa. In identifying this gap, the objective of this study was to investigate whether a community-based dance organisation, the Wilvan School of Dance, was an inclusive innovation contributing to social change. The research focused on the period of Wilvan's existence between 1968, when it was formed and 1994, when the first democratic election in South Africa was held. This was simultaneously a period of extreme repression as well a period of mass resistance to Apartheid. The study used a qualitative research design focused on a case study, the Wilvan School of Dance, using hermeneutic phenomenology, an approach which made allowance for my subjectivity, as the primary methodology, given that I had been a student at this dance school over a period of 21 years between its formation in 1968 and 1989. This was supported by a grounded theory approach to the gathering of data, which was primarily through interviews with 20 plus stakeholders and associates of the Wilvan School of Dance. The value of the study is in its contribution to understanding how a micro-organisation interpreted and contributed to social change and how individuals involved with this community-based dance organisation acted as agents of social change catalysing an inclusive social innovation within marginalised communities during the repressive governance framework of Apartheid. In addition, the significance of the study lies in its contribution to scholarship on social innovation, social change and justice.